Daniel Bonge : Om lax och laxfångst - Danell, Kjell; Svanberg, Ingvar (2022)
In 23 June 1730, Daniel Herman Bonge (1706−1777), born in Oulo in contemporary Finland, defended a thesis about the natural history of the salmon (Salmo salar) at Uppsala University. The thesis, consisting of 28 pages, was written under the presidium of the Professor Lars Roberg. Bonge was apparently familiar with the salmon from his home province and provided many first-hand insights in salmon biology and salmon fishing. He was able to critically discuss the information in ancient sources. In the dissertation, there were also several woodcuts that depict various kinds of gear used by fisher peasants in northern Finland for capturing salmon. Bonge’s dissertation is still of interest for scholars, especially the ethnographic descriptions he gives about the fishing. He also provides local ichthyonyms in Swedish and Finish used in Ostrobothnia. A contemporary writer, Professor Bernd Roling, comments upon Bonge’s dissertation that it is written in ”a very personal and indeed Finnish manner”, and that it gives us insights into the cultural and conditions of Ostrobothnia and Kemi Lappmark in the early eighteenth century. Bonge’s dissertation was followed by other scientifi c descriptions of salmon and salmon fishing in Sweden, also still of historical interest. In 1745, an article by the Tornedalian and astronomer Anders Hellant (1717–1789) about the reproduction of the salmon in northern Swedish rivers, was published in the Proceedings of the Swedish Academy of Sciences. Beside Bonge and Hellant, we can especially mention the provincial physician in Västernorrland Nils Gissler (1715–1771), who in 1751 discusses salmon and salmon fishing in detail in an article in the same journal. The salmon was of course of great local and national economic interest, whichled several scientists to study it in detail from different perspectives.